Treatment outcomes in mild traumatic brain injury: a systematic review of randomized controlled trials. (28th July 2020) - Arbabi, M; Sheldon, RJG; Bahadoran, P; Smith, JG; Poole, N; Agrawal, N
ABSTRACT: Objectives: Mild traumatic brain injury (mTBI) is a controversial and under-researched area, despite most traumatic brain injuries being classed as mild. Our objective was to review the evidence underpinning these approaches to treat mTBI including educational, psychological, rehabilitative and pharmacological approaches and discuss their efficacy. Methods: A systematic review of literature was carried out using Web of science, Scopus, Medline, Pubmed, Cinahl, and PsychInfo databases. Randomized Controlled Trials (RCTs) looking at treatment outcome in mTBI for adults were included, published between 1980 and 2019. Methodological quality of the studies was reviewed using the Scottish Intercollegiate Guideline Network (SIGN) checklist for RCTs. Results: Searches identified 3993 studies, of which 25 met inclusion criteria, and a total number of participants of 3213. Mean age was 35, and 59% male. Ten studies had <100 participants, 15 studies 100–395. Studies were grouped into education and early intervention, rehabilitation (8), psychological interventions (4), and pharmacotherapy (4). Inconsistency of definitions and outcome measures used precluded meta-analysis. Conclusions: Traditional education and reassurance can no longer be recommended as having the best evidence base for efficacy as compared to psychological and rehabilitative approaches, and guidelines should begin to reflect this.